2008
DOI: 10.1111/j.1939-1676.2008.0127.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 12‐Lead Electrocardiogram for Differentiating Paroxysmal Supraventricular Tachycardias in Dogs

Abstract: Electrocardiographic criteria used in people for differentiating SVT can also be applied in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 54 publications
3
28
2
3
Order By: Relevance
“…The OAVRT rate under general anesthesia was significantly slower, (median, 274 bpm; range, 207‐411 bpm). Whether evaluating the awake or anesthetized OAVRT rates in our study, they are faster than in a previously reported group of 14 dogs, in which the anesthetized OAVRT rate was 229 ± 42 bpm . Whereas focal atrial tachycardias (FAT) had faster ventricular rates than OAVRT in that study, median OAVRT rate in our awake dogs was substantially higher and median OAVRT rate in our anesthetized dogs was the same as the anesthetized mean FAT ventricular rate (278 bpm) in the prior study.…”
Section: Discussioncontrasting
confidence: 54%
“…The OAVRT rate under general anesthesia was significantly slower, (median, 274 bpm; range, 207‐411 bpm). Whether evaluating the awake or anesthetized OAVRT rates in our study, they are faster than in a previously reported group of 14 dogs, in which the anesthetized OAVRT rate was 229 ± 42 bpm . Whereas focal atrial tachycardias (FAT) had faster ventricular rates than OAVRT in that study, median OAVRT rate in our awake dogs was substantially higher and median OAVRT rate in our anesthetized dogs was the same as the anesthetized mean FAT ventricular rate (278 bpm) in the prior study.…”
Section: Discussioncontrasting
confidence: 54%
“…2 Moreover the presence of P 0 waves inscribed within the STeT segment with a short RP 0 interval and a RP 0 /P 0 R < 1 suggests the presence of an OAVRT. 4,5 An exception to this occurs in case of pre-excited atrial fibrillation, with absence of P waves and broad QRS complexes; however in this condition the RR intervals are constantly irregular. 16 Other conditions in which P 0 waves with short RP 0 intervals can appear inscribed within the STeT segment are atrioventricular nodal reentrant tachycardia with a slowefast electrophysiologic behavior, rapid focal atrial tachycardias with significant first degree AV block.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the origin of the tachycardia, the rapid retrograde ventriculo-atrial conduction (short RP 0 intervals), make it very probable that the anatomic substrate of the SVT was an atrioventricular accessory pathway (AP) inducing an atrioventricular macroreentrant circuit (orthodromic atrioventricular reciprocating tachycardia [OAVRT], or accessory atrioventricular pathwaymediated tachycardia). 4,5 As a matter of fact, on the second sinus beat, a negative P 0 wave is evident on the ST segment (second black arrow), suggesting the presence of retrograde conduction of the stimulus through the accessory pathway without the subsequent orthodromic conduction across the atrioventricular node, preventing the macroreentrant circuit formation and the subsequent recurrence of the tachycardia. Image interpretation: Fig.…”
mentioning
confidence: 96%
“…The negative P waves buried within the ST segment, as seen in lead II, are related to the posteroseptal location of the accessory pathway that is usually found in OAVRT, allowing each ventricular depolarization to spread toward the atrium [6] [7] [8]. In a study that investigated paroxysmal supraventricular tachycardias in dogs, a simultaneous 12-lead surface ECG was used and was identified significant differences between the polarity of P waves in leads II, III, aVR, Open Journal of Veterinary Medicine aVF, and V3 to V6 when OAVRT and focal atrial tachycardia were compared [15]. In this case, although the standard 6-lead ECG system was used instead, P wave polarities were similar to the most common findings of the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%